Feeling Blue or Seeing Red? Similar Patterns of Emotion Associations With Colour Patches and Colour Terms. (January 2020) - Jonauskaite, Domicele; Parraga, C. Alejandro; Quiblier, Michael; Mohr, Christine
For many, colours convey affective meaning. Popular opinion assumes that perception of colour is crucial to influence emotions. However, scientific studies test colour–emotion relationships by presenting colours as patches or terms. When using patches, researchers put great effort into colour presentation. When using terms, researchers have much less control over the colour participants think of. In this between-subjects study, we tested whether emotion associations with colour differ between terms and patches. Participants associated 20 emotion concepts, loading on valence, arousal, and power dimensions, with 12 colours presented as patches ( n  = 54) or terms ( n  = 78). We report high similarity in the pattern of associations of specific emotion concepts with terms and patches ( r  = .82), for all colours except purple ( r  = .−23). We also observed differences for black, which is associated with more negative emotions and of higher intensity when presented as a term than a patch. Terms and patches differed little in terms of valence, arousal, and power dimensions. Thus, results from studies on colour–emotion relationships using colour terms or patches should be largely comparable. It is possible that emotions are associated with colour concepts rather than particular perceptions or words of colour.